Treatment Option for Abernethy Malformation—Two Cases Report and Review of the Literature - Lin, Yuese; Li, Xuandi; Li, Shujuan; Ba, Hongjun; Wang, Huishen; Zhu, Ling (Frontiers in Pediatrics, 2020)
Background: Abernethy malformation is a rare vascular anomaly of the portal venous system, which is also known as congenital portosystemic shunts(CPSS).The clinical manifestations can be serious, including hepatopulmonary syndrome(HPS),which can lead to significant hypoxemia and cyanosis. Case Presentation:Here we report two cases of patients with Abernethy Malformation.Case 1 was a 6-year-old boy whose blood oxygen saturation was 78%.Case 2 was a 6-year-old girl who had a history of open heart surgery and residual cardiac left to right shunt,whose blood oxygen saturation was 83%.These two children with unexplained cyanosis were diagnosed pulmonary arteriovenous fistula by contrast echocardiography with agitated saline.Selective retrograde catheter angiography confirmed the presence of portosystemic shunt.Case 1 was with type I Abernethy malformation,he did not receive any specific treatment and could only wait for liver transplantation.Case 2 was with type II Abernethy, she underwent tanscatheter closure of the CPSS and a 20mm-diameter,14mm-long Vascular Plug (SHSMA Inc, Shanghai, China) was used to occlude the shunt. Results:In case 1,the boy developed a deteriorating cyanosis and dyspnea on exertion. In case 2, her exercise tolerance improved after shunt closure, during a follow-up of 3 years,her blood oxygen saturation increased from 83% to 98%. Conclusion:The results indicate special emphasis on attention to those children with unexplained cyanosis.Since these patients may have abernethy malformation, and part of them could be treated by transcatheter occlusion and have a good outcome, the key is the how to diagnose and carefully assess.